Herpes simplex virus 1 as an oncolytic viral therapy for refractory cancers - Scanlan, Hayle; Coffman, Zachary; Bettencourt, Jeffrey; Shipley, Timothy; Bramblett, Debra E. (Frontiers in Oncology, 2022)
The need for efficacious and non-toxic cancer therapies is paramount. Oncolytic viruses (OVs) are showing great promise and are introducing new possibilities in cancer treatment with their ability to selectively infect tumor cells and trigger antitumor immune responses. Herpes Simplex Virus 1 (HSV-1) is a commonly selected OV candidate due to its large genome, relative safety profile, and ability to infect a variety of cell types. Talimogene laherparevec (T-VEC) is an HSV-1-derived OV variant and the first and only OV therapy currently approved for clinical use by the United States Food and Drug Administration (FDA). This review provides a concise description of HSV-1 as an OV candidate and the genomic organization of T-VEC. Furthermore, this review focuses on the advantages and limitations in the use of T-VEC compared to other HSV-1 OV variants currently in clinical trials. In addition, approaches for future directions of HSV-1 OVs as cancer therapy is discussed